Analisis keterampilan berpikir kritis peserta didik SMA kelas X IPA pada materi virus - Agustine, Jussi; Nizkon, Nizkon; Nawawi, Sulton (Assimilation: Indonesian Journal of Biology Education, 2020)
This study aims to determine the critical thinking skills of class X science students in Talang Ubi District on virus material. Type of quantitative descriptive research. The population of all students of class X Science in Talang Ubi District. The sample used in class X IPA 1 in SMA Negeri 1 Talang Ubi, SMA Negeri 2 Unggulan Talang Ubi, and SMA YKPP Pendopo. Data collection techniques using purposive sampling. Retrieval of data using instruments about the ability to think critically on virus material using the framework developed by Facione (2013), consist of five indicators namely: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results of the study of Critical Thinking Ability in the District of Talang Ubi can be categorized as low, with a percentage value of 59.26%. For the average number of indicators obtained in Talang Ubi District, namely: interpretation indicator has a percentage of 87.94%, and analytical indicator of 60.27%, and evaluation indicator of 45.52%, an inference indicator of 52.83%, an explanatory indicator by 40.00% and self-regulation indicators by 69.01%. This study can be concluded that the critical thinking ability of high school students of class X IPA in Talang Ubi sub-district on virus material is categorized as low. These results indicate that strategies, teaching materials, and learning media need to be developed to facilitate students' thinking skills.